Penerapan Pembelajaran Berdiferensiasi dalam Menulis Teks Cerita Fantasi Siswa Kelas VII - Rini Dwi Haryati; Sufanti, Main; Huda, Miftakul (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
The purpose of this study is to describe the design of differentiated learning in writing fantasy narrative texts at SMP Negeri 4 Surakarta City. This study employed a qualitative descriptive approach with 31 students of class VII C as the research subjects. Data collection techniques included observation, interviews, documentation, and analysis of students’ assessment results. The data analysis technique used in this study was qualitative analysis. As stated by Miles and Huberman (Sugiyono, 2018), data analysis includes data collection, data reduction, data display, and conclusion drawing. The results of the study indicate that the differentiated learning design consists of planning, implementation, and evaluation stages. In the planning stage, the teacher prepares teaching modules according to students’ learning needs. In the implementation stage, the teacher conducts learning activities based on students’ levels of understanding (low, medium, and high). During the learning process, the teacher applies differentiation in content, process, and product by providing different materials, activities, and levels of challenge while still referring to the same learning objectives. In the evaluation stage, the teacher uses diagnostic, formative, and summative assessments to monitor students’ progress and overall learning outcomes. Differentiated learning is proven to be effective in creating inclusive and meaningful learning and in providing equal opportunities for each student to develop according to their potential and learning needs.